2010
DOI: 10.1136/bmj.c2649
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of AS03B adjuvanted split virion versus non-adjuvanted whole virion H1N1 influenza vaccine in UK children aged 6 months-12 years: open label, randomised, parallel group, multicentre study

Abstract: Objectives To compare the safety, reactogenicity, and immunogenicity of an adjuvanted split virion H1N1 vaccine and a non-adjuvanted whole virion vaccine used in the pandemic immunisation programme in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 24 publications
10
123
1
1
Order By: Relevance
“…Our study and a similar study in children, 91 reveal heightened immunogenicity of AS03 A -adjuvanted vaccine in comparison with WV vaccine by HI and MN. Waddington et al 91 did not measure antibodies after the first vaccine dose or assess vaccine immunogenicity using CHMP criteria.…”
Section: Chaptermentioning
confidence: 67%
“…Our study and a similar study in children, 91 reveal heightened immunogenicity of AS03 A -adjuvanted vaccine in comparison with WV vaccine by HI and MN. Waddington et al 91 did not measure antibodies after the first vaccine dose or assess vaccine immunogenicity using CHMP criteria.…”
Section: Chaptermentioning
confidence: 67%
“…Both, adjuvanted and non-adjuvanted, vaccines were well tolerated. [10][11][12] Nevertheless, literature shows that after vaccination with adjuvanted pandemic influenza vaccines, such as Pandemrix ® , the incidence of local reactions and systemic AEs was higher than after vaccination with non-adjuvanted pandemic influenza vaccines. 13 In children, especially the occurrence of fever was much higher.…”
Section: Discussionmentioning
confidence: 99%
“…13 In children, especially the occurrence of fever was much higher. 10,11 In the children who participated in our study, high proportions of fever were reported. Besides the role of the adjuvant, there were some other possible explanations for these high rates of fever.…”
Section: Discussionmentioning
confidence: 99%
“…70,71,81 A wider variety of events have been reported in children. 79,80 However, the frequency of occurrence of the AEs is not significantly different from subjects administered a placebo or an ECE-derived vaccine.…”
Section: Introductionmentioning
confidence: 98%
“…67,70,71,79 The most frequently reported local AEs have been pain at injection site (10-43% of the subjects), followed by redness, swelling, induration and ecchymosis. 67,70,71,[79][80][81] Total systemic AEs have been reported in 18-51% of the subjects, 65,68,69 the most common being headache, fatigue, myalgia and malaise (3-20% of the subjects) in adults as well as the elderly. 70,71,81 A wider variety of events have been reported in children.…”
Section: Introductionmentioning
confidence: 99%